Analysis of factors affecting the choice of intercity interprovincial transportation modes (Makassar-Palu route service case) - Muhammad Firdaus Kamil; Lambang Basri Said; Ilham Syafei (Jurnal Scientia, 2024)
In the modern era, transportation is a basic need for all humans to be able to move from one place to another. In Indonesia, there are various types of transportation modes to help people or passengers move from their place of origin to their destination. Choosing the right mode of transportation is very important to meet the desired needs. One of the aspects reviewed in the analysis of transportation needs and services is the choice of transportation mode. Choice of mode occurs as a result of the need for movement, and movement occurs because of the process of fulfilling needs. Based on the problem formulation in this research, namely analyzing the factors that influence the choice of inter-city, inter-provincial (AKAP) transportation modes on the Makassar - Palu route. This research involves five variables as influencing factors, namely: X1; Travel Costs, X2: Service Level, X3: Travel Time, X4: Accessibility and X5: Reliability Level. The research method used is the Statistical Package for Social Science Ver.21 software. The results obtained are based on the Regression Equation Model, as follows: Y = -2.470 + 0.223X1 + 0.358X2 + 0.184X3 + 0.119X4 + 0.307X5. Based on the results of the analysis in this research, it can be seen that the influence of the factors or variables achieved is, X2: Service Level, X5: Reliability, X1: Travel Costs, X3: Travel Time, X4: Accessibility.